(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article examines the emergence of ideology in society, a conceptual analysis of the previous theory of ideology in the scientific aspect, with a full-fledged study of its objects, and research problems in the humanities.